Diagnostic Accuracy and Reliability of Ultrasonography for the Detection of Fatty Liver: A Meta-Analysis - Hernaez, Ruben (2011)
Ultrasonography is a widely accessible imaging technique for the detection of fatty liver, but the reported accuracy and reliability have been inconsistent across studies. We aimed to perform a systematic review and meta-analysis of the diagnostic accuracy and reliability of ultrasonography for the detection of fatty liver. We used MEDLINE and Embase from October 1967 to March 2010. Studies that provided cross-tabulations of ultrasonography versus histology or standard imaging techniques, or that provided reliability data for ultra-sonography, were included. Study variables were independently abstracted by three reviewers and double checked by one reviewer. Forty-nine (4720 participants) studies were included for the meta-analysis of diagnostic accuracy. The overall sensitivity, specificity, positive likelihood ratio, and negative likelihood ratio of ultrasound for the detection of moderate-severe fatty liver, compared to histology (gold standard), were 84.8% (95% confidence interval: 79.5-88.9), 93.6% (87.2-97.0), 13.3 (6.4-27.6), and 0.16 (0.12-0.22), respectively. The area under the summary receiving operating characteristics curve was 0.93 (0.91-0.95). Reliability of ultrasound for the detection of fatty liver showed kappa statistics ranging from 0.54 to 0.92 for intrarater reliability and from 0.44 to 1.00 for interrater reliability. Sensitivity and specificity of ultrasound was similar to that of other imaging techniques (i.e., computed tomography or magnetic resonance imaging). Statistical heterogeneity was present even after stratification for multiple clinically relevant characteristics. CONCLUSION: Ultrasonography allows for reliable and accurate detection of moderate-severe fatty liver, compared to histology. Because of its low cost, safety, and accessibility, ultrasound is likely the imaging technique of choice for screening for fatty liver in clinical and population settings.